2016
DOI: 10.4236/ajps.2016.76084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Radish (<i>Raphanus sativus</i>) Genotypes under Different Saline Regimes

Abstract: An effective and simple screening technique for identification of salt tolerant and salt sensitive radish genotypes was observed. Sand is used as potting media. Six genotypes of radish were used for screening against four salinity levels (0, 1, 3, 5 and 7 dS/m −1 ). Twenty days old seedlings of radish were salinized with salt solution (NaCl). Morphological, physiological and ionic parameters were studied. Radish genotypes Laal-Pari and 40 Days executed the best performance in all the measured attributes and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…No effect of genotypes was observed on leaf chlorophyll content of the radish crop (Table 3). This behavior was not observed by Ayyub et al (2016), who tested six radish cultivars and found differences in this parameter. The increase in chlorophyll content provides greater development of chloroplasts and consequent addition in leaf nitrogen content (Piekielek & Fox, 1992;Smeal & Zhang, 1994).…”
Section: Resultsmentioning
confidence: 68%
“…No effect of genotypes was observed on leaf chlorophyll content of the radish crop (Table 3). This behavior was not observed by Ayyub et al (2016), who tested six radish cultivars and found differences in this parameter. The increase in chlorophyll content provides greater development of chloroplasts and consequent addition in leaf nitrogen content (Piekielek & Fox, 1992;Smeal & Zhang, 1994).…”
Section: Resultsmentioning
confidence: 68%
“…Such results can be justified by the presence of salts in the soil solution, reducing the water absorption capacity of the plants and causing water stress as the saline concentration increased because, in this situation, the main defense mechanism of the plants includes A, gs, Ci and E (Parihar et al, 2015), which is why these variables are directly related and presented similar behaviors, negatively affecting the photosynthetic apparatus of the radish and, consequently, yield. Ayyub et al (2016), evaluating different radish genotypes under saline stress, emphasized that stomatal conductance decreased with an increasing salinity, where a lower stomatal condutace was observed with a conductivity of 7 dS m -1 and that the main effect of salinity is a reduction of photosynthetic processes. Sousa et al (2016b), evaluating gaseous exchanges in citrus irrigated with saline waters, observed a reduction of gs, A, E and internal efficiency of carboxylation as the ECw increased from 0.6 to 3.0 dS m -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, a decrease in chlorophyll content caused by salinity has been reported by many researchers [ 22 , 27 , 28 ]. Otherwise, some authors [ 29 , 30 ] affirm that salinity reduces the chlorophyll content in salt-sensitive plants and increases it in salt-tolerant ones. Our data, in the control group, agree with those by Alamgir and Ali [ 31 ], which showed an increase in chlorophyll content in rice plants exposed to salt stress.…”
Section: Discussionmentioning
confidence: 99%